2008
DOI: 10.2465/jmps.071020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of SiO2 Raman spectrum indicating the transformation from coesite to quartz in Gföhl migmatitic gneisses in the Moldanubian Zone, Czech Republic

Abstract: The Raman spectroscopy of more than 2000 SiO 2 inclusions in zircon separates from Gföhl migmatitic gneisses in the Nové Dvory area shows that most of the SiO 2 inclusions are composed of quartz with clear and intense peaks at 464, 393, 266, 207 and 125 cm -1 . It also reveals that a few SiO 2 inclusions have a weak but clear peak at 521 cm -1 , which is the most fundamental vibration of coesite, along with typical quartz vibrations mentioned above. The Raman spectrum is composed of the intense vibrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Conversely, the appearance of the new peak at 520 cm −1 in the quartz spectrum is not a thermal effect associated with the power of the laser. This peak is characteristic of coesite and corresponds to the symmetric stretching of oxygen in the four‐membered SiO 4 tetrahedra . However, the Raman spectrum of coesite is normally characterised by additional peaks at 204, 270, 355 and 426 cm −1 , which were not present in our sample .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the appearance of the new peak at 520 cm −1 in the quartz spectrum is not a thermal effect associated with the power of the laser. This peak is characteristic of coesite and corresponds to the symmetric stretching of oxygen in the four‐membered SiO 4 tetrahedra . However, the Raman spectrum of coesite is normally characterised by additional peaks at 204, 270, 355 and 426 cm −1 , which were not present in our sample .…”
Section: Discussionmentioning
confidence: 99%
“…Geothermo-barometric calculations suggest that several eclogite and garnet peridotite masses in the Gföhl unit experienced UHP conditions (e.g., Nakamura et al, 2004;Medaris et al, 2006;Naemura et al, 2009). On the other hand, evidence for UHP metamorphism of felsic granulite and gneiss in the Bohemian Massif is rare, but a few findings of microdiamond and coesite from such felsic rocks have been recently reported (e.g., Kobayashi et al, 2008;Kotková et al, 2011;Perraki and Faryad, 2014), indicating that some garnet peridotite masses and surrounding felsic rocks may have shared the same P-T history, although peak P-T conditions of granulite in the Gföhl unit have been estimated to be approximately 1.6-2.0 GPa, 900-1100°C (e.g., Carswell and O'Brien, 1993).…”
Section: Geological Outlinementioning
confidence: 99%
“…Mineralogical (increase in Ca of garnet from core to rim; Nakamura et al, 2004) and geochemical (e.g., positive Sr and Eu anomalies; Obata et al, 2006) characteristics of kyanite -bearing eclogites from this body suggest that at least some of them should have experienced subduction before the attainment of the UHP conditions of about 5 GPa, 1100 °C. Kobayashi et al (2008) found some peaks reflecting coesite relics in Raman spectra for SiO 2 inclusions in zircon that were extracted from the migmatitic gneiss near the Nové Dvory peridotite body, although the P -T path of the migmatitic gneiss of the Gföhl unit is still under debate (e.g., Cooke and O'Brien, 2001).…”
Section: Geological Settingmentioning
confidence: 99%